Web-based rehabilitation interventions for people with rheumatoid arthritis: A systematic review - Srikesavan, C; Bryer, C; Ali, U; Williamson, E (SAGE Publications, 2018)
Background Rehabilitation approaches for people with rheumatoid arthritis include joint protection, exercises and self-management strategies. Health interventions delivered via the web have the potential to improve access to health services overcoming time constraints, physical limitations, and socioeconomic and geographic barriers. The objective of this review is to determine the effects of web-based rehabilitation interventions in adults with rheumatoid arthritis. Methods Randomised controlled trials that compared web-based rehabilitation interventions with usual care, waiting list, no treatment or another web-based intervention in adults with rheumatoid arthritis were included. The outcomes were pain, function, quality of life, self-efficacy, rheumatoid arthritis knowledge, physical activity and adverse effects. Methodological quality was assessed using the Cochrane Risk of Bias tool and quality of evidence with the Grading of Recommendations Assessment, Development and Evaluation approach. Results Six source documents from four trials ( n = 567) focusing on self-management, health information or physical activity were identified. The effects of web-based rehabilitation interventions on pain, function, quality of life, self-efficacy, rheumatoid arthritis knowledge and physical activity are uncertain because of the very low quality of evidence mostly from small single trials. Adverse effects were not reported. Conclusion Large, well-designed trials are needed to evaluate the clinical and cost-effectiveness of web-based rehabilitation interventions in rheumatoid arthritis.